2017
DOI: 10.1093/mnras/stw3309
|View full text |Cite
|
Sign up to set email alerts
|

The properties of energetically unbound stars in stellar clusters

Abstract: Several Milky Way star clusters show a roughly flat velocity dispersion profile at large radii, which is not expected from models with a tidal cut-off energy. Possible explanations for this excess velocity include: the effects of a dark matter halo, modified gravity theories and energetically unbound stars inside of clusters. These stars are known as potential escapers (PEs) and can exist indefinitely within clusters which are on circular orbits. Through a series of N -body simulations of star cluster systems,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 75 publications
5
60
1
Order By: Relevance
“…Our analysis reveals flattened velocity dispersion profiles starting from the tidal radius (≈ 40 pc) until beyond the Jacobi radius, settling around values of ∼ 2.5−4 km s −1 , with an average velocity dispersion along the two components of 3.5 ± 0.9 km s −1 at the Jacobi radius. This is in tension with what expected from the presence of potential escapers stars (Claydon et al 2017) at a ∼3-sigma confidence level. However, note that we cannot exclude that small-scale systematics in the Gaia DR2 catalog could still produce an inflation of the velocity dispersion profiles of the order of < 1 km s −1 .…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…Our analysis reveals flattened velocity dispersion profiles starting from the tidal radius (≈ 40 pc) until beyond the Jacobi radius, settling around values of ∼ 2.5−4 km s −1 , with an average velocity dispersion along the two components of 3.5 ± 0.9 km s −1 at the Jacobi radius. This is in tension with what expected from the presence of potential escapers stars (Claydon et al 2017) at a ∼3-sigma confidence level. However, note that we cannot exclude that small-scale systematics in the Gaia DR2 catalog could still produce an inflation of the velocity dispersion profiles of the order of < 1 km s −1 .…”
Section: Resultscontrasting
confidence: 61%
“…Fukushige & Heggie 2000;Küpper et al 2010;Daniel et al 2017). The number of potential escapers is comparable to the number of bound stars around 0.5 r j and dominates at larger radii (Claydon et al 2017). As a result, they produce a flattening of the velocity dispersion profile.…”
Section: Flattening Of the Velocity Dispersion Profilesmentioning
confidence: 93%
See 1 more Smart Citation
“…In the outer parts of globular clusters, where a larger fraction of stars are nonmembers, the approach used by Scarpa et al is likely to overestimate the velocity dispersion. The agreement with our models could probably be improved further since the simulations presented here do not include tidal fields, which increase the velocity dispersion of stars near the tidal radius (Küpper et al 2010;Claydon, Gieles & Zocchi 2015).…”
Section: Intermediate-mass Black Holessupporting
confidence: 57%
“…We simulated the orbits of the globular clusters using the spray-particle implementation by Küpper et al (2012), where the escape velocity was modified to match that observed in N-body simulations with realistic tidal fields (Claydon et al 2017). We assume a Milky Way potential similar to the best-fit Palomar 5 model , but with a Jaffe bulge.…”
Section: Globular Clustersmentioning
confidence: 99%